Impact of a Clinical Communication Skill Training Course on the Knowledge of Iranian Dental Students : Communication Skill Course for Dental Students - Mandana Naseri; Mohammad Ali Mozayeni; Behzad Amooee; Amiri, Maryam (Journal of Dental School, 2023)
Objectives Communication skills are key element of dental practice. In this study, we aimed to evaluate the effects of a communication skill training course on the verbal, listening, and feedback skills of dental students. Methods A total of 42 (20 males and 22 females) third-year dental students of the School of Dentistry of Shahid Beheshti University of Medical Sciences (Tehran, Iran) were enrolled in this study and asked to complete the Burton GE questionnaire before and after the clinical communication skill training course. The students were instructed through lectures, case-based scenarios, and group discussions. The questionnaire consisted of 18 questions in three dimensions of listening, verbal, and feedback skills, with each area including six questions. The reliability coefficient was determined by measuring Cronbach’s alpha coefficient. The validity of the questionnaire was also investigated in this study. The collected data were analyzed using paired t-test. Results The mean total score of the students increased from 17.07 to 22.17 for the verbal skills, from 11.80 to 15.21 for the listening skills, and from 16.55 to 21.76 for the feedback skills. There were significant improvements in the students’ verbal (P<0.001), listening (P<0.001), and feedback skills (P<0.001) after their participation in the communication skill training course. No sex predilection was observed in the baseline and final results. Conclusion communication skill training courses could have remarkable effects on the improvement of verbal, listening, and feedback skills of dental students.